Employee Involvement and Work Culture - JAIN, VIPIN; CHAWLA, CHANCHAL; ARYA, SATYENDRA (The journal of contemporary issues in business and government, 2021)
This paper illustrates the relationship betweenemployee participation in problem- solving and decision making and perceived administrative performance. Concurrently, the concept of employee participation was studied by implanting it within the perspective of a national belief. The operative use of employee participation is confidently related to superficial administrative performance. More specifically, employee involvement and empowerment plans, and the habit of self-handling teams have a straight noteworthy link to the decision-making perception of the administrative performance. According to the results obtained, the enterprises are cheered to adopt employee participation agendas to boost performance, competitiveness and growth on the local and international marketplace.